Vloga socialnih partnerjev pri urejanju in organiziranju delovnega časa - Počivavšek, Jakob Krištof (Delavci in delodajalci, 2016)
The article methodically presents the regulation of certain institutes of working hours at different levels of regulation. Particular emphasis is given to the role of social partners, especially trade unions, in determining the basis for the regulation and organisation of working hours both, through collective agreements as well as through other instruments which the social partners are bound to oblige to on the grounds of legislation regarding the working hours. The article exposes some of the dilemmas and problems occurring in practice; it further outlines the working hours related challenges brought about by technological progress.
Keywords: delodajalci; delovni čas; kolektivne delovne pogodbe; sindikati; socialno partnerstvo